Porosity analysis of two acrisols by X-ray computed microtomography - Dowuona, G.N.N.; Taina, I.A.; Heck, R.J. (Soil Science, 2009)
Porosity and void characteristics of two major Acrisols (Ferric Acrisol and a Ferri-Plinthic Acrisol) with contrasting pedogenic features from the humid forest zone of Ghana were studied by X-ray computed microtomography. Spatial variability of the porosity of the two Acrisols, as well as the volume of different classes of void size, shape, and orientation, was quantitatively determined. Variations in the void characteristics were interpreted in correlation with the pedogenic features of the two soils. The Ferri-Plinthic Acrisol, with more numerous roots, faunal burrows, and with smaller amounts of rock fragments than the Ferric Acrisol, exhibited a larger total pore volume. The greatest part of the pore volume in the two soils could be associated with the macrovoids class. There was a strong correlation between void size and shape. Regular voids corresponded in general to mesovoids of biogenic origin, especially in the surface horizons, whereas irregular and elongated voids were composed mostly of macrovoids. Void orientation was predominantly inclined, with the exception of the horizons where the root or fauna advancement was impeded by a dense subjacent horizon. Considering soil-vegetation relationships, the computed microtomography imagery showed that root development in the lower horizons of the Ferric Acrisol was probably impeded by Fe-Mn nodules; cultivation of Crotalaria juncea on this soil probably facilitated the root penetration in some of the denser zones within the profile. The Ferri-Plinthic Acrisol structure could be improved by the extensive root system of Chromolaena odorata, a self-established fast-growing perennial shrub. Management strategies of the two major soils need to take into account relevant information on pore distribution, morphology, and orientation. Copyright © 2009 by Lippincott Williams & Wilkins, Inc.
Keywords: Acrisols; Porosity; Void classes; X-ray computed microtomography